Pelaksanaan dakwah Persatuan Islam Tionghoa Indonesia (PITI) di Medan Sumatera Utara: Kajian tentang masalah dan cabaran / Abdi Syahrial Harahap - Abdi Syahrial, Harahap (2015)
The research is aimed at investigating the Indonesian dakwah organization of Muslim Tionghoa or known as Persatuan Islam Tionghoa Indonesia (PITI) which is located at Medan District, North Sumatera-Indonesia, mainly regarding its existence as organization of dakwah, its strategy, problems and challenges as well as its effort to make the dakwah more effective and efficient. Qualitative case study was employed as the method to arrive at the conclusions of the study. While, survey was employed to support qualitative data as second sources. Document analyses, observations and interviews with six members of the organization and an observer of Muslim Tionghoa had been conducted upon which data were analyzed by employing thematic analysis and coding. The findings indicate that the PITI as an asset of Islamic movement had contributed to bridge the psychological transition especially for muallaf who faced their hindrances among their family and community because of the change of their belief and convert to Islam. Islamic teaching was a special program offered by PITI to help muallaf to enforce their belief and to enhance their knowledge regarding Islam. PITI also developed its strategy to establish the existence of the organization whether through networking and making relationship with the other Islamic organization such as Muhammadiyyah, NahdhatulUlama (NU) and al-Washliyah or through assimilation and developing diverse cultural approach among various communities. PITI also develops integrated method accordingly in the dakwah based on demands and needs through combination manners of dakwah bil hall (good performance), hikmah (wise), jadal (debate) and qishash (history). The internal and external problems which are faced by PITI include leadership and management, availability of infrastructure and human resources, financial sources, ethnic identity, cultural and habitual old life and Christianization, while an effort to make dakwah more effective is to solve the problems mentioned. Therefore, PITI plans to reshuffle structurally and administratively of the organization, establishing financial sources such as setting up bureaus of trade and travel and employing electronically mass media and publishing as a medium of dakwah.